PENGARUH PERMAINAN TRADISONAL PETAK JONGKOK TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK PERTIWI DESA TERATE KECAMATAN SIRAH PULAU PADANG OKI - Lestari, Widya; Fahmi, Fahmi; Cindrya, Elsa; Fitri, Izza (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
The purpose of this study was to determine the effect of traditional games of squatting on gross motor skills of children aged 5-6 years. The research method is the Experimental Method with the type of Pre-Experimental Designs with the design One Group Pretest-Posttes Designs. The population of this study were group B children totaling 13 people. The observation is group B children aged 5-6 years. The results of the research and discussion are that there is an increase in gross motor skills in children, it can be said that in this study there is a significant effect given the traditional game activities of squatting plots, this is shown in the experimental post-test using relay games. Before the application of squatting traditional game activities, children with low gross motor skills were 6 children, while the medium value was 7 children. After applying the traditional game activities of squatting plots, the value of children's gross motor skills is very good 2 people and motor skills develop as expected there are 6 children, and the value starts to develop only 5 children, which means that after being given treatment, children's gross motor skills increase than before treatment, and these activities improve the gross motor skills of early childhood.